2002
DOI: 10.1080/00224490209552128
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors and the sexuality of pregnant and postpartum women

Abstract: This study examined the influence of role quality, relationship satisfaction, fatigue, and depression on women s sexuality during pregnancy and after childbirth. Questionnaire data were obtained from 138 women pregnant with their first child, of whom 104 responded at 12 weeks postpartum, and 70 responded at 6 months postpartum. Women reported significant reductions in sexuality during pregnancy and postpartum. Relationship satisfaction explained levels of sexual satisfaction during pregnancy, and was a predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
164
0
30

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(203 citation statements)
references
References 35 publications
9
164
0
30
Order By: Relevance
“…Since dyspareunia and sexual dysfunction are strongly associated with personal experiences and relationship factors [2], the question of bother in this study covers just part of this complexity. Few studies address level of bother and the ones which do show conflicting results regarding impact on sexual life in the postpartum months [4,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since dyspareunia and sexual dysfunction are strongly associated with personal experiences and relationship factors [2], the question of bother in this study covers just part of this complexity. Few studies address level of bother and the ones which do show conflicting results regarding impact on sexual life in the postpartum months [4,10].…”
Section: Discussionmentioning
confidence: 99%
“…Dyspareunia occurring during pregnancy and childbirth may be a result of morphological and hormonal changes of the pelvic floor [8,3,6], and has shown to correlate with delivery mode [6,9]. In women breastfeeding, a reduction in estrogen may lead to reduced vaginal lubrication as a response to sexual stimulation [10]. The relationship between the pelvic floor muscles (PFM) and dyspareunia is poorly understood, and the existing literature in pregnant and postpartum women is sparse.…”
mentioning
confidence: 99%
“…The analysis of each FSFI domain showed a decrease in sexual desire, arousal, vaginal lubrication, orgasm and sexual satisfaction from the second to the third trimester of gestation, as well as greater discomfort or pain related to the sexual activity. Several studies have reported similar results and attributed them to a series of factors such as: body changes that affect self-esteem, discomfort, fear of harming the baby and physical symptoms as nauseas, sleepiness and fatigue 16,[26][27][28][29][30][31][32][33] . Some authors stipulated a total FSFI score of 26.5 as the cut-off score between women with and without sexual dysfunction 34 .…”
Section: Sexual Functionmentioning
confidence: 76%
“…Apesar de a gestação advir da sexualidade, estudos apontam a influência da primeira sobre a última por diversos fatores, tais como a alteração na imagem corporal, a mudança de papéis sociais, a qualidade do relacionamento, as alterações hormonais, entre outros [14][15][16] .…”
Section: Introductionunclassified